2011
DOI: 10.5539/ies.v4n4p230
|View full text |Cite
|
Sign up to set email alerts
|

A Confirmatory Factor Analysis of Motivated Self-regulated Learning Questionnaire in an EFL Context

Abstract: The Motivated Strategies for Learning Questionnaire (MSLQ) is an instrument for measuring motivation and learning strategies in general education. This instrument is modular, consisting of motivation and learning strategies modules. This study sought to see whether the learning strategies module of this instrument can be applied to the context of English Language Learning (EFL). For this purpose, the instrument was administered to a group of Iranian EFL college students (n=190) as well as a group of Iranian co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Researchers in the field of language education have also showed interest in the application of the MSLQ. The validity of the MSLQ in an EFL context was examined by, Ayatollahi, Rasekh, and Tavakoli (2011) who conducted a confirmatory factor analysis (CFA) of the learning strategies module of the instrument and found identical factor structures for EFL and general education contexts; they suggested that MSLQ is a valid measurement instrument in determining EFL college students' study strategies as well. Huang (2008) also studied the reliability and applicability of the MSLQ to foreign language learning contexts and reported that "in spite of some inherent uniqueness, L2 learning is similar to other subjects in the school environment and the MSLQ has the potential to be applied to L2-related studies" (p. 529).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in the field of language education have also showed interest in the application of the MSLQ. The validity of the MSLQ in an EFL context was examined by, Ayatollahi, Rasekh, and Tavakoli (2011) who conducted a confirmatory factor analysis (CFA) of the learning strategies module of the instrument and found identical factor structures for EFL and general education contexts; they suggested that MSLQ is a valid measurement instrument in determining EFL college students' study strategies as well. Huang (2008) also studied the reliability and applicability of the MSLQ to foreign language learning contexts and reported that "in spite of some inherent uniqueness, L2 learning is similar to other subjects in the school environment and the MSLQ has the potential to be applied to L2-related studies" (p. 529).…”
Section: Discussionmentioning
confidence: 99%
“…El objetivo del proceso de adecuación es que el instrumento traducido y adaptado tenga propiedades psicométricas comparables al instrumento original [233]. El MSLQ, al día de hoy, ha sido traducido, adaptado y administrado a estudiantes de países como: Argentina [234], Australia [235], Brasil [236], China [237], Colombia [164], Croacia [238], Egipto [239], España [22,240,241], Irán [242], Japón [243], México [244], Suráfrica [245], Turquía [246], Estados Unidos [247], entre otros.…”
Section: Metas Y Preguntas De Investigaciónunclassified